Pengaruh Substitusi Abu Daun Nanas Terhadap Workabilitas, Densitas, dan Kuat Tekan Beton Normal - Ahmad Junaidi; Adji Sutama; Verinazul Septriansyah (Department of Civil Engineering, Diponegoro University, 2025)
The increasing demand for concrete in the construction industry has led to high cement production, contributing to global CO₂ emissions. This research examines the potential of pineapple leaf ash as a partial cement substitution material to produce more environmentally friendly concrete. An experimental study was conducted with seven variation percentages of pineapple leaf ash substitution (0%, 7.5%, 10%, 12.5%, 15%, 17.5%, and 20%) by cement weight, using 150x300 mm cylindrical specimens. Testing included workability, density, and concrete compressive strength at 28 days. The results showed that slump values decreased with increasing percentages of pineapple leaf ash, from 9.5 cm in normal concrete to 3.0 cm at 20% substitution. Concrete density increased from 2250 kg/m³ in normal concrete to a maximum value of 2335 kg/m³ at 12.5% substitution, then decreased at higher percentages. Optimal compressive strength was achieved at 12.5% substitution with a value of 34.70 MPa, increasing 22.79% compared to normal concrete (28.26 MPa). This research concludes that the optimal pineapple leaf ash substitution is at 12.5%, resulting in significant improvements in concrete density and compressive strength, although with a decrease in workability that must be considered in its application.